Water management in the Basin of Mexico: current state and alternative scenarios - Carrera-Hernández, Jaime J; Gaskin, S. J (Hydrogeology journal, 2009)
Water management policies in the Basin of Mexico, where Mexico City and its nearly 20 million inhabitants live, are analyzed. After a brief description of how water has been managed, possible water management plans that would change water management practices in the Basin are discussed and a call is made for a change in the defensive attitude towards water taken to date. As the aquifer's replacement cost is considered to be the proxy for the implementation of water tariffs, this is determined, based on the cost of future water sources, and found to be 0.65-0.72 USD/m³. This is twice the amount currently charged in the Federal District (0.34 USD/m³), where 45% of the City's domestic water users are found. As another alternative, the development of an artificial recharge program is also analyzed and found to be a plausible way to increase water supply at a unitary cost of 0.605 USD/m³. Despite the presence of these alternatives, it is suggested that water management in the Basin needs to change from a water supply approach to a water demand approach.